Pengelolaan Limbah Botol Plastik : Mengubah Sampah Menjadi Rupiah - Muhamad Haqqi Maulana; Nazwa Cintana Hezzel Wibowo; Novi Puspitasari; M. Fajar Ardi P.; Rizky Luky Oktafandi; Cinditya Wahyu Infantri; Arif Rizal Abadi; Diyan Sri Wahyuningsih; Arya Narinda W; Riski Hanafi (Institut Teknologi dan Bisnis Semarang, 2025)
The Community Service Program (KKN) aims to enhance the community’s awareness and ability to improve welfare and quality of life, as well as to contribute to the development of the target area. One of the issues faced by Blondo Village is the abundant plastic bottle waste. A potential solution to address this issue is by repurposing plastic bottle waste into products with market value. This approach not only helps reduce excessive plastic waste but also improves the local economy. Therefore, KKN Untidar Blondo Village, Period II, Academic Year 2024/2025, organized a socialization program on recycling plastic bottles, turning waste into economic value. This program seeks to tackle the issue of excessive plastic bottle waste. With proper knowledge and training on waste management, plastic waste will no longer be a concerning problem.